BELIEFS AND PRACTICES ABOUT RABBIT IN ALEVI-BEKTASHI TRADITION - Ünsal Yılmaz YEŞİLDAL (Fırat University, 2020)
Religious beliefs are the facts that direct the life of mankind and sometimes reach the conservatism dimension by combining with different non-religious elements and limit the people. Some of these beliefs are entirely based on religious facts, while others are superstitions embellished with religious realities. These beliefs, both in the practices of people's daily lives and in the public narratives, have been living among the people for centuries. While some of these beliefs show national characteristics, others have universal properties. Some of the beliefs that contain national motives may vary according to sectarian and/or textural differences within the same nation. Turks have been a neighbor of the religions and neighbors with different belief systems throughout their history. Even today, some Turks belong to religions other than Islam, unlike others. The Turks in the Islamic Circle are also included in different sectarians and/or texturals. Some of the Turkmens referred to by their experts as Alevi, Bektashi and Kızılbaş are among the leading of these types of communities. These concepts are often referred to together throughout the study as it is a matter beyond the content of our study to distinguish or explain these three terms. As it is known, some of the beliefs that are religious or related to religion cause taboo beings and behaviors. One of these beings or behaviors is the beliefs and attitudes that people develop about the animals they see around them. Among the Turks, wolf/gray wolf and deer are accepted as totems in Western terminology, and ancestors / animals are the main ones in Turkish intellectual life. Although there are no ancestry and maternity features, one of the animals accepted as totems among Turks is a rabbit. In this study, the beliefs of Alevi-Bektashi societies about the rabbit and their attitudes based on these beliefs will be tried to go down to their archaic origins in comparison with their counterparts in the world, and the determinations of these beliefs and attitudes about the rabbit will be revealed. In this way, Turks' view of the rabbit through different beliefs throughout history will be revealed.